The Effect of Clinical Pharmacist Intervention in Optimizing Colistin Use at Huu Nghi Viet Tiep Hospital - Thi Thu Trang, Tran; Thi Hien, Nguyen; Thang Toan, Nguyen; Thi Thu Thuy, Nguyen; Thi Thuy Van, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 3, 2024)
An intervention study was conducted to evaluate the effectiveness of clinical pharmacy interventions in optimizing the management of colistin use at Huu Nghi Viet Tiep Hospital. These interventions were classified according to the Ministry of Health guidance at Decision No. 3547/QĐ-BYT. This study conducted 226 patients in the baseline period (January-December 2021, the pre-intervention group), and 80 patients in the intervention implementation period (December 2022 -March 2023, the intervention group). Clinical pharmacists performed 119 interventions for 65/80 patients (81.3%). The majority of interventions were related to monitoring (code C4, 36.1%), followed by interventions related to the change in therapy (code C1, 29.4%). The acceptance rate of the change in therapy interventions by physicians was 77.1%; while with the other interventions, this rate was 100% (including the codes C2-need further reference, C3-provide information, and C4-monitoring). Eight interventions were not accepted (3 indication-related interventions, 5 dosing-related interventions). The concordance rate for indications was significantly higher in the intervention group than in the pre-intervention group (96.3% vs 77.0%, p<0.001). Compared to the pre-intervention group, the rate of loading doses and maintenance doses in accordance with the Guideline in the intervention group were also higher (96.3% vs 22.3%, 98.7% vs 30.2%, respectively). Both differences were statistically significant (p<0.05). The duration of colistin also significantly decreased (median 9 days vs 7 days, p<0.05). The study results revealed the positive impact of clinical pharmacy interventions on colistin usage at the hospital and the need for training and exchanging among healthcare workers to optimize colistin use, especially in severe patients.